PENGARUH CORPORATE GOVERNANCE, UKURAN PERUSAHAAN, LEVERAGE, DAN FAKTOR LAINNYA TERHADAP MANAJEMEN LABA - Yesi Lestari; Umar Issa Zubaidi (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this research is to obtain empirical evidence regarding 9 independent variables on 1 dependent variable. The independent variable consists of the influence of institutional ownership, managerial ownership, board of commissioners meeting frequency, audit committee meeting frequency, board size, company size, leverage, audit quality, and profitability on the dependent variable is earnings management through discretionary accruals in manufacturing firms in Indonesia. The object used in this research is all manufacturing firms listed in Indonesian Stock Exchange (IDX) during research period 2017-2019. Samples in this research are obtained through purposive sampling method, in which 158 data samples are selected after meeting the sampling criteria. Multiple linear regressions and hypotheses testing are used as data analysis method in this research. The result of this research shows that profitability have influences towards earnings management. But institutional ownership, managerial ownership, board of commissioners meeting frequency, audit committee meeting frequency, board size, company size, leverage, and audit quality do not have any influences towards earnings management.